The Importance of Different Biomes (Atlantic Forest, Cerrado, and Caatinga) in the Regional Structuring of Neotropical Dragonfly Assemblages - Karolina Teixeira; Acácio de Sá Santos; Diogo Silva Vilela; Cíntia Ribeiro; Marciel Elio Rodrigues (Diversity)
Understanding how assemblages are structured is important for ecology, especially in tropical regions that exhibit high biodiversity and are currently experiencing high rates of loss and modification of natural environments caused by anthropogenic impacts. Understanding the structuring of assemblages across different regions at different spatial scales allows us to comprehend how environmental modifications can affect biodiversity on a local and regional scale. The objective of this study was to evaluate the biodiversity of Odonata species using taxonomic diversity metrics (richness and composition) in areas of Cerrado, Atlantic Forest, and Caatinga and to evaluate which sets of local and spatial environmental variables are associated with these assemblages among the different areas evaluated. The study was conducted in the state of Bahia, where 49 streams were sampled, including 17 in the Atlantic Forest, 18 in the Caatinga, and 15 in the Cerrado. Our results demonstrate a high diversity of Odonata species, with 95 species collected. We found a similar species richness among the regions sampled. However, each region presented a distinct composition, with greater similarity between the Cerrado and the Caatinga. Spatial predictors along with some environmental variables were associated with the Caatinga and Cerrado. Some environmental variables, such as the amount of riparian vegetation and aquatic vegetation, were associated with the Cerrado. The results highlighted that each of the evaluated regions are fundamental for maintaining and conserving the regional dragonfly biodiversity. The lack of conservation of aquatic ecosystems in the different regions leads to local species loss and, consequently, to a loss of regional Odonata biodiversity.